The history of the book in 100 books the complete story, from Egypt to e-book - Cave, Roderick; Ayad, Sara (Firefly Books (U.S.) Inc., 2014)
Each of the 100 books chosen has played a critical role in the development of books in all their forms and with all that they bring: literacy, numeracy, technological progress and the expansion of scientific knowledge, religion, political theory, entertainment, and more.